The Effect of Eight Weeks of Soy Supplementation and Aerobic Exercise on Lipid Profile in Overweight Women with Type 2 Diabetes - Mohsen Akbarpur; Fazlollah Fathollahi Shoorabeh *; Mahdi Fahimi; Sara Peisbaz (Lorestan University of Medical Sciences, 2020)
Background and Aim: This study examines the impact of eight weeks of aerobic exercise and soy supplementation on lipid profiles in overweight women with type 2 diabetes. Materials and Methods: In this semi-experimental study, 40 women with type 2 diabetes and the mean age of 50.07±1.03 and the mean fat percentage of 30.75±0.37 were purposefully selected and then randomly divided into four groups: aerobic training + soybean, aerobic + placebo, soybean and control. The aerobic exercise program included three sessions per week with an intensity of 60-72% of maximum heart rate for eight weeks. Supplemental groups received one soy pill daily (containing50 mg of isoflavone) for eight weeks. Blood samples were collected in order to examine the variables investigated during fasting conditions in the pre and post-test phases. Data analysis was carried out using one-way ANOVA and t-test with significant the level (P≤0.05) using SPSS16 software. Results: Serum levels of triglyceride and HDL-c in the aerobic + soybean, aerobic and soybean groups from the pre-test to post-test phase significantly decreased. Serum levels of cholesterol and LDL-c in the aerobic + soybean and soybean group decreased (p≤0.05). However, these values were not remarkably altered in the training group (p≥0.05). Moreover, there was a significant difference in the serum levels of triglyceride and LDL-c in the aerobic + soybean and soybean groups with the control group. There was a significant distinction between HDL-c levels in all three experimental groups (p≤0.05). Conclusion: The results of lipid profiling showed that aerobic exercise and soy supplementation had positive impacts on the lipid profiles of overweight women with type 2 diabetes